The United Kingdom and the Netherlands maternity care responses to COVID-19: A comparative study. Issue 1 (February 2023) - van den Berg, Lauri M.M.; Balaam, Marie-Clare; Nowland, Rebecca; Moncrieff, Gill; Topalidou, Anastasia; Thompson, Suzanne; Thomson, Gill; de Jonge, Ank; Downe, Soo; ,; Downe, Soo; Ellison, George; et al.
Abstract: Background: The national health care response to coronavirus (COVID-19) has varied between countries. The United Kingdom (UK) and the Netherlands (NL) have comparable maternity and neonatal care systems, and experienced similar numbers of COVID-19 infections, but had different organisational responses to the pandemic. Understanding why and how similarities and differences occurred in these two contexts could inform optimal care in normal circumstances, and during future crises. Aim: To compare the UK and Dutch COVID-19 maternity and neonatal care responses in three key domains: choice of birthplace, companionship, and families in vulnerable situations. Method: A multi-method study, including documentary analysis of national organisation policy and guidance on COVID-19, and interviews with national and regional stakeholders. Findings: Both countries had an infection control focus, with less emphasis on the impact of restrictions, especially for families in vulnerable situations. Differences included care providers' fear of contracting COVID-19; the extent to which community- and personalised care was embedded in the care system before the pandemic; and how far multidisciplinary collaboration and service-user involvement were prioritised. Conclusion: We recommend that countries should 1) make a systematic plan for crisis decision-making before a serious event occurs, and that this must include authentic service-user involvement, multidisciplinary collaboration, and protection of staff wellbeing 2) integrate women's and families' values into the maternity and neonatal care system, ensuring equitable inclusion of the most vulnerable and 3) strengthen community provision to ensure system wide resilience to future shocks from pandemics, or other unexpected large-scale events.